Investigation of the Performance of Nikhilam Multiplication Algorithm. (3rd July 2015) - Eyupoglu, Can
Abstract: Multiplication is one of the most important operations in computer arithmetic. Multiplication is used in many operations such as squaring, division and computing reciprocal. Moreover, multiplication is a very significant arithmetic operation for lots of signal processing applications which are convolution, correlation, frequency analysis, image processing etc. The efficiency of multiplication operation is crucial for the process time of these applications. Nikhilam algorithm is one of the algorithms developed for increasing the efficiency and reducing the cost in order to simplify multiplication. In this work, the performance of Nikhilam multiplication algorithm is analyzed in terms of the number of multiplication and the total process time for different bit lengths.